It takes a village: how plant-associated bacterial communities socialise to shape plant growth and health - Carmen Escudero-Martínez; Andrzej Tkacz; Marta Albareda; Carmen Sánchez-Cañizares (Essays in Biochemistry, 2026)
Abstract Plants outsource many functions to an associated microbiome, an ‘outside gut’ composed of socially interacting bacterial communities that support plant growth and health. These dynamic and diverse microbiomes span different plant microenvironments and form complex networks shaped by the environmental context and the plant’s genetics. While some microbes cause disease, many others contribute to essential functions, influencing plant fitness, survival, and ultimately soil health. Although the host genetics and abiotic factors structure these communities, the functional diversity and ecological roles of plant-associated bacteria are ultimately shaped by microbe–microbe interactions. These interactions also play a critical role in the successful colonisation of plant tissues. Beneficial members of these communities enhance plant nutrient uptake, modulate phytohormones to shape root architecture, or prime plant systemic immunity to repel pathogens. Deciphering how plant-associated bacterial communities assemble and interact, both with their host and with one another, is essential for uncovering the mechanisms that underpin bacterial social behaviours within the plant holobiont, such as quorum sensing, metabolite exchange, and contact-dependent interactions. Here we review several recent publications that shed new light on the social lives of plant-associated bacteria, with a particular focus on their competition mechanisms and strategies for colonisation and establishment. In this context, we highlight how the rational design of plant bioinoculants based on microbial consortia represents a powerful strategy for promoting sustainable agriculture in a rapidly changing environment.